2016
DOI: 10.1017/s0022463416000291
|View full text |Cite
|
Sign up to set email alerts
|

Connecting prehistoric and historic cultures in Southeast Asia

Abstract: Linking the early historic cultures of Southeast Asia to their prehistoric antecedents has, despite some decades of research, proved difficult for a number of reasons. Until the 1960s, this did not seem to be an issue for scholars of the region. For George Coedès, the region was simply occupied by diverse and backward ethnic and linguistic communities, cultivators using stone tools, or at best, people using bronze with poorly developed social organisations until impacted by the expanding Han peoples during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Some propose that it began 13,000 to 4,000 years ago, but many others debunk this, theorizing that it is actually more recent. [12][13][14][15] Every piece of literature reviewed shares similar conclusions. It can be inferred that there is a relationship between the habit of chewing betel nuts and dental health, whether in the context of modern or prehistoric society.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some propose that it began 13,000 to 4,000 years ago, but many others debunk this, theorizing that it is actually more recent. [12][13][14][15] Every piece of literature reviewed shares similar conclusions. It can be inferred that there is a relationship between the habit of chewing betel nuts and dental health, whether in the context of modern or prehistoric society.…”
Section: Discussionmentioning
confidence: 85%
“…Based on archaeological evidence found in Bacau, East Timor, betel nut chewing likely started 13,000 to 4,000 years ago. 12 Later research suggested the age of this tradition might be around 2,500 years, which implies the tradition is more recent than previously thought. 13 Given the uncertainty surrounding the origination date of the betel nut chewing tradition, further research is needed to verify and confirm the date when humans started chewing betel nuts.…”
Section: Introductionmentioning
confidence: 97%